GENDER DIFFERENCES IN ENGLISH TEACHERS COMMUNICATION PATTERN AT SMPN 1 PETANGBADUNG REGENCY - Meiyana Ariss Susanti, I Luh (Universitas Pendidikan Ganesha, 2018)
In this study, the researcher would like to investigate the types of reinforcements used by male and female teacher, the frequency of using reinforcements both male and female teacher, and to whom it is usually addressed by each teacher. The concern of this study, there were two subjects chosen, one male and one female English teacher. The data was collected through observation and interview. The result of the study showed that those teachers are the same in using the types of reinforcement; they applied praise and negative reinforcement. In term of frequency of using reinforcement, female teachers applied more often than male teachers. Male and female teacher tended to reinforce them who were active in the classroom without regarding the students? gender. In responding to reinforcement given, mostly students responded by smiling and becoming more active in the following the next lesson. In certain cases, male student showed different responses, particularly when they received negative reinforcement in term of point reducing and withdrawing certain image that they had.